Impact of the detection of ζ-globin chains and hemoglobin Bart's using immunochromatographic strip tests for α0-thalassemia (-SEA) differential diagnosis - Supansa Pata (2020)
© 2019 Pata et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. α0-Thalassemia is an inherited hematological disorder caused by the deletion of α-globin genes. The Southeast Asian deletion (-SEA) is the most common type of α0-thalassemia observed in Southeast Asian countries. Regarding WHO health policy, an effective α0-thalassemia screening strategy is needed to control new severe α-thalassemia cases. In this study, a monoclonal antibody panel was used to develop immunochromatographic (IC) strip tests for detecting the Hb Bart's and ζ-globin chain. Among 195 samples, all α0-thalassemia traits (78 α0-thalassemia (-SEA) and 4 α0-thalassemia (-Thai)) had low MCV or MCH values. The sensitivity, specificity, PPV and NPV of the IC strip tests for ζ-globin and Hb Bart's for screening α0-thalassemia (-SEA) within the low MCV or MCH samples were 100%, 65.2%, 90.7%, 100% and 96.2%, 47.8%, 86.6%, 78.6%, respectively. All 4 α0-thalassemia (-Thai) traits were negative for ζ-globin chains but positive for Hb Bart's using the IC strip tests. These results led to a α0-thalassemia screening being proposed in which blood samples are first evaluated by MCV, MCH and Hb typing. Samples with high MCV and MCH values are excluded for the presence of the α0-thalassemia gene. Samples with low MCV or MCH values are assayed using the developed IC strip tests, where only samples testing positive are further assayed for α0-thalassemia by PCR. Patients with Hb H, EA Bart's or EF Bart's diseases do not need to use this IC strip assay. Thus, in this study, a simple and cost effective α0-thalassemia point of care test was developed.